2016
DOI: 10.1111/imj.13156
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Queensland physicians and the influence of rural exposure on practice location

Abstract: The Queensland branch of the Royal Australasian College of Physicians (RACP) commissioned this study to update their workforce profile and examine rural practice. The present investigation aimed to describe characteristics of Queensland physicians and determine the influence of childhood and training locations on current rural practice. A cross-sectional online survey, conducted 4 July-4 November 2013, was administered to Fellows of The RACP, Queensland. Descriptive statistics report characteristics and logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Our study also confirms the increased likelihood of rural practice among physicians who either had a rural childhood background or were trained overseas, consistent with other studies 8,9 . However, increasing evidence suggests the importance of rural training immersion experiences to improving geographic distribution of the post‐Fellowship workforce 32,33 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study also confirms the increased likelihood of rural practice among physicians who either had a rural childhood background or were trained overseas, consistent with other studies 8,9 . However, increasing evidence suggests the importance of rural training immersion experiences to improving geographic distribution of the post‐Fellowship workforce 32,33 .…”
Section: Discussionsupporting
confidence: 90%
“…Encouragingly, however, it suggests that work location does not affect their professional satisfaction. A 2013 Queensland report provides further positive evidence of the professional satisfaction of rural specialist physicians 9 . Professional satisfaction, the extent to which a workplace matches a worker’s aspirations or expectations, is associated with individual and organisational outcomes and has important implications for medical workforce planning 10,11 .…”
Section: Chapter 1 Characterising Australia’s Rural Specialist Physician Workforce: the Professional Profile And Professional Satisfactiomentioning
confidence: 99%
“…A 10 year longitudinal cohort study from Australia showed that rural exposure during medical training related to rural work. 51 Another important factor reported elsewhere as a determinant of RR practice uptake is rural background [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] , but in this study it was not associated with or predictive for rural practice location. However, rural born and rural living experiences were associated with the preference of future rural practice location also intention to remain in RR practice.…”
Section: Discussionmentioning
confidence: 60%
“…Improved coordination of rurally interested medical graduates with rural training capacity and pathways to specialty colleges is a key objective of university‐based RTHs 40 . These address evidence demonstrating that low selection rates of rurally experienced or rural‐focused graduates in a specialty strongly correlates with the expected geographical distribution of that workforce 41 …”
Section: Discussionmentioning
confidence: 85%